Is late thrombolysis effective for subacute renal vein thrombosis in patients with nephrotic syndrome? a case report - Silva, Johann Vargas (2020)
Renal vein thrombosis (RVT) associated with nephrotic syndrome (NS) in patients with flank pain is rarely the earliest manifestation. Despite the absence of formal guidelines, treatment generally consists of prophylaxis against new thrombotic events and clot dissolution (thrombolysis) or clot removal (thrombectomy). We describe the case of a 25-year-old woman with lumbar pain, nausea and vomiting, who developed nephrotic proteinuria, macroscopic hematuria and loss of renal function requiring hemodialysis without improvement with methylprednisolone and cyclophosphamide. Considered diagnoses of systemic lupus erythematosus (SLE) and antiphospholipid antibody syndrome (APS). Angiotomography showed subacute vena cava thrombosis with extension to the two renal veins. Alteplase thrombolysis was performed to recovery of renal function. Patient progressed with improvement of renal function and discontinuation of hemodialysis. In conclusion, late thrombolysis may be effective for subacute RVT in NS patients.